2019
DOI: 10.1038/s41390-018-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Absence of gut microbial colonization attenuates the sympathoadrenal response to hypoglycemic stress in mice: implications for human neonates

Abstract: BACKGROUND: Gut microbiota plays an important role during early development via bidirectional gut-brain signaling. Catecholamines provide a survival advantage allowing adaptation to common postnatal stressors. We aimed to explore the potential link between gut microbiota/gut-derived metabolites and sympathoadrenal stress responsivity. METHODS: The effect of insulin-induced hypoglycemia was compared in mice with (control, adapted control) and without microbiome (germ-free, GF). Counter-regulatory hormones were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…Takino T et al [13] pointed that the relative abundance of Firmicutes (including its families, such as Lactobacillaceae ), which supports health and immune function, was increased substantially during the first week after birth. Giri P et al [12] observed that the sympathoadrenal function could be affected by lack of a microbiome or microbial metabolites, leading to inferior health status. In our data, more than three fourths of patients in group A received surgery on the first day after birth, which means that they had more time for the bowel and intestinal microbiome to develop in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takino T et al [13] pointed that the relative abundance of Firmicutes (including its families, such as Lactobacillaceae ), which supports health and immune function, was increased substantially during the first week after birth. Giri P et al [12] observed that the sympathoadrenal function could be affected by lack of a microbiome or microbial metabolites, leading to inferior health status. In our data, more than three fourths of patients in group A received surgery on the first day after birth, which means that they had more time for the bowel and intestinal microbiome to develop in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Early operation leads to earlier repair and restoration, providing additional time for the bowel to recover and develop in the neonatal period. Animal experiments showed that lack of a microbiome could impair adrenal catecholamine, implying that the poor health status of neonates might be caused by immature of intestinal function [12]. However, the choice of surgical method remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Lower systolic blood pressure and pulse pressure, blunted ventilatory responsiveness to hypercapnia and disrupted brainstem neurochemistry were observed in rats after chronic broad-spectrum antibiotic intervention (O'Connor et al, 2019). A recent study by Giri, Hu, La Gamma, and Nankova (2019) reported that mice raised in a germ-free environment with the absence (Hosoi, Okuma, Matsuda, & Nomura, 2005). Interleukin-1 has been shown to cause a vagusdependent decrease in hypoxic ventilatory response in neonatal rat pups (Balan et al, 2011).…”
Section: Gastrointestinal Maturation and Signalling To The Brainmentioning
confidence: 99%
“…Lower systolic blood pressure and pulse pressure, blunted ventilatory responsiveness to hypercapnia and disrupted brainstem neurochemistry were observed in rats after chronic broad‐spectrum antibiotic intervention (O'Connor et al., ). A recent study by Giri, Hu, La Gamma, and Nankova () reported that mice raised in a germ‐free environment with the absence of a microbiome and, consequently, short‐chain fatty acids had an impaired adrenal catecholamine response to hypoglycaemia. Dysbiosis may influence excitation of cells in the nucleus tractus solitarii, a central processing site in the brain for autonomic function.…”
Section: Late‐onset Infectionmentioning
confidence: 99%
“…One previous finding found that the absence of gut microbial colonization selectively impaired catecholamine response to hypoglycemic stress in mice. ( Giri, Hu, La Gamma, & Nankova, 2019 )…”
Section: Introductionmentioning
confidence: 99%